Desenvolvimento de eletrodos com materiais nanoestruturados para determinação de corantes de cabelo - Oliveira, Ricardo Alexandrino Guimarães de [UNESP] (2013)
The hair dyes represent an important area of the cosmetic industry and are used by 50% of the female population worldwide. In recent years there has been a growing concern with the use regulations and the permitted limit for these compounds due to dermatological effects, mutagenic and carcinogenic and associated with its use. As a result the demand for reliable analytical methods for the control of the level of dyes in aqueous media are extremely important. Thus, the present work describes the construction and characterization of two electrodes developed by modification with nanostructured materials (TiO2 and CNT). In the case of electrodes modified with TiO2 nanotubes, these were grown on plates as Ti substrate and its application in the identification and quantification of hair dye Basic Brown 17 in tap water using the technique of linear sweep voltammetry. Already the Multi Wall Carbon Nanotubes were used in the modification of a glassy carbon electrode and applied in determining the hair dye Acid Green 25 in aqueous medium. For Basic Brown 17 dye, an analytical curve was obtained over the concentration range 1.0 x 10-6 to 1.0 x 10-4 mol L-1, the following equation: Ip (mA) = 47.7 mA / mol-1 [MB - 17] - 2.8 x 10-6 mA, r = 0.9952, n = 7. The limit of detection (LOD) and quantitation (LOQ) was 1.3 x10-7 mol L-1 and 4.4 x10-7 mol L-1, respectively. The method was applied to contaminated tap water fortified with 12 mg L-1 dye and will undergo analysis using the method of standard addition. The mean recovery (n = 5) was 99.4 ± 1.4%. For the dye Acid Green 25 a calibration curve was constructed using square wave voltammetry in the range 1.0 x10-7 to 2.0 x 10-6 mol L-1 and pre-accumulation of 10 min following equation: Ip = 42.7 μA/mol L-1 [VA - 25] - 5.1 x 10-6 μA, r = 0.9998, reaching limits of detection and quantification of 2.7 x10-9 mol L-1 and 8.9 x10-9 mol L-1, respectively. The method was applied in tap water spiked...